In welchen Betrieben verdienen Frauen mehr? Der Einfluss betrieblicher Statusrelationen auf die geschlechtsspezifische Lohnungleichheit; In which firms do female workers earn more? The influence of status relations in the firm on the gender wage gap - Michael Schweiker (Industrielle Beziehungen, 2017)
Dieser Beitrag untersucht, inwiefern die geschlechtsspezifische Lohnungleichheit in Deutschland von statusbasierten Ansprüchen im Betrieb abhängig ist. Grundsätzlich sollte sich die geschlechtsspezifische Lohnungleichheit verringern, wenn sich der Status von Frauen im Betrieb relativ zu ihren männlichen Kollegen erhöht. Es werden zwei Indikatoren für diese betrieblichen Statusrelationen entlang der Geschlechtskategorie betrachtet: Frauenanteil im Management und Unterschiede zwischen den Geschlechtern beim Besitz von Hochschulabschlüssen. Mit der Verdienststrukturerhebung von 2010 und Multilevel Modellen kann gezeigt werden, dass sich der relative Lohn von Frauen mit steigendem Frauenanteil im Management und mit zunehmenden Vorteilen beim Besitz von Hochschulabschlüssen erhöht. Diese positiven Effekte auf den Lohn von Frauen variieren zudem entlang der Lohnverteilung: Bildungsvorteile von Frauen wirken sich stärker positiv auf hohe Löhne aus, während der Frauenanteil im Management eher unteren Lohngruppen hilft. Schließlich sind die Effekte stärker ausgeprägt in Betrieben ohne Tarifbindung. – – Relational inequality theory suggests that status-based claims on organizational resources are a central mechanism leading to wage inequality at the workplace. Following this theory the paper examines the relationship between status-based claims in the firm and the gender wage gap in Germany. In general, it is expected that wage inequality between women and men decreases, when the status of women increases relative to male coworkers in the firm. I look at two indicators of status relations along the gender category: share of females in management and differences in the share of university degrees in the firm. Using the German Structure of Earnings Survey 2010 and employing multi-level regression models I find that the gender wage gap decreases with an increasing share of females in management and with growing differences between the sexes in the share of university degrees. In addition, these positive effects on the wage of female employees vary along the wage distribution: The effect of advantages in university degrees is stronger for higher wages, whereas the share of female managers predominantly helps low wage groups. Finally, the effects are stronger in firm with individual wage determination compared to firms that are covered by a collective agreement.
Keywords: D310; D330; J310; J510; 330; geschlechtsspezifische Lohnungleichheit; Theorie relationaler Ungleichheit; Statusrelationen; Tarifbindung; Betriebe; gender wage gap; relational inequality theory; categorical status distinctions; coverage by collective wage agreements; work organizations